Neuropharmacology of light-induced locomotor activation - Amato, Davide; Pum, Martin E.; Groos, Dominik; Lauber, Andrea C.; Huston, Joseph P.; Carey, Robert J.; Silva, Maria A. De Souza; Müller, Christiane (Neuropharmacology, 2015)
Presentation of non-aversive light stimuli for several seconds was found to reliably induce locomotor activation and exploratory-like activity. Light-induced locomotor activity (LIA) can be considered a convenient simple model to study sensory-motor activation. LIA was previously shown to coincide with serotonergic and dopaminergic activation in specific cortical areas in freely moving and anesthetized animals. In the present study we explore the neuropharmacology of LIA using a receptor antagonist/agonist approach in rats. The non-selective 5-HT2-receptor antagonist ritanserin (1.5-6 mg/kg, i.p.) dose-dependently reduced LIA. Selective antagonism of either the 5-HT2A-receptor by MDL 11,939 (0.1-0.4 mg/kg, i.p.), or the 5-HT2C-receptor by SDZ SER 082 (0.125-0.5 mg/kg, i.p.), alone or in combination, had no significant influence on LIA. Also the selective 5-HT1A-receptor antagonist, WAY 100635 (0.4 mg/kg, i.p.) did not affect LIA. Neither did the preferential dopamine D2-receptor antagonist, haloperidol (0.025-0.1 mg/kg, i.p.) nor the D2/D3-receptor agonist, quinpirole (0.025-0.5 mg/kg, i.p.) affect the expression of LIA. However, blocking the glutamatergic NMDA-receptor with phencyclidine (PCP, 1.5-6 mg/kg, i.p.) dose-dependently reduced LIA. This effect was also observed with ketamine (10 mg/kg, i.p.). These findings suggest that serotonin and dopamine receptors abundantly expressed in the cortex do not mediate light-stimulus triggered locomotor activity. PCP and ketamine effects, however, suggest an important role of NMDA receptors in LIA.
EVALuna2:23682